STRUCTURE OPTIMIZATION OF POLYMER-BASED NANOFIBER MULTILAYER MEMBRANES USING ELECTROSPINNING FOR AIR FILTRATION - Insan Kamil, Aji
The widespread use of polymer plastics in daily life has led to new problems, including non-degradable waste and environmental pollution. One potential solution to these issues is the production of nanofibers, which have numerous advantages. The most versatile and commonly used method to produce nanofibers is electrospinning. While relatively practical, the electrospinning process is complex due to the various variables involved. This study aims to investigate the parameters affecting the morphology of nanofibers produced by electrospinning and to modify the structure of the nanofiber membrane to produce an air filter. The parameters investigated include solution flow rate (????), electric current (????), and viscosity (????) from various polymeric solutions, namely polyacrylonitrile (PAN), acrylonitrile butadiene styrene (ABS), and polylactic acid (PLA). These parameters have a notable impact on the determination of fiber diameter. Fiber diameter (????????) and ????/???? exhibit power law relations with power scales of 0.535, 0.066, and 0.440 for PAN, ABS, and PLA, respectively). The relationship between ???????? and ? also produced power law with power scale of 0.10 for PLA and 0.23 for ABS. The nanofiber mat demonstrates relatively good mechanical properties and hydrophobic surface for ABS and PLA and a hydrophilic one for PAN. Furthermore, the membrane structure is modified by combining two layers of nanofiber mats with different diameters and packing densities based on the filtration efficiency, pressure drop, and quality factor evaluated by the models from literature. The models could be used to provide a starting point for assessing fibrous filter performances. The modified membrane outperforms its constituent nanofiber, with a pressure drop of 61.73 Pa at 5.3 cm s-1 face velocity, filtration efficiency of >95.56%, and quality factor of >0.052 Pa-1.